The Effect of Self-Efficacy and Optimism toward Quality of Life on Transfemoral Prosthesis Users in Indonesia - Rachmat, Nur; Fanani , Mohammad; Darsono, Darsono; Suwarto, Suwarto (Advances in Social Sciences Research Journal, 2020)
Purpose: In persons with amputations, their quality of life decreases tremendously as a consequence of complex physical and psychological problems after losing an important part of their bodies. Therefore, a holistic and comprehensive rehabilitation approach post-amputation is needed to improve individual mobility and to help reintegrate into society. Method: This is a cross-sectional study involving 110 individuals with the transfemoral prosthesis. Data were collected using questionnaires and documentation and were analyzed using Multiple Linear Regressions. Results: Findings revealed a significantly positive effect of self-efficacy on quality of life (p<0.001) and of optimism on quality of life (p=0.001). Moreover, there is also a significant positive effect of self-efficacy and optimism together on the quality of life (p<0.001). Conclusion: to improve quality of life of transfemoral prosthesis users, it is recommended to consider the role of persons’ self-efficacy and optimism.